What Drives Generation Z’s Financial Behaviors? The Influence of Financial Literacy, Financial Socialization, and Self-Control - Hafizha, Agnifa Isna; Arifin, Zaenal (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study aims to examine the influence of financial literacy, financial socialization, and self-control on the financial behaviors of Generation Z.Method: This research employs a quantitative approach, utilizing an online questionnaire distributed through Google Forms to university students. The sample was selected using a purposive sampling technique, resulting in 185 respondents. The collected data was analyzed using multiple linear regression and t-test, with the assistance of SPSS software version 2.6.Result: The findings indicate that financial socialization and self-control significantly positively affect the financial behaviors of Generation Z. In contrast, financial literacy does not have a significant impact on these behaviors among university students. This suggests that external influences, such as parental guidance or peer discussions, and personal traits like self-discipline, play a more dominant role in financial decision-making than mere financial knowledge.Practical Implications for Economic Growth and Development: This study contributes by fostering better financial behaviors among Generation Z, who will soon enter the workforce and drive economic activities. By highlighting the importance of financial socialization and self-control, the research provides insights for policymakers and educators to design targeted financial education programs that enhance financial decision-making. In the long run, improved financial behaviors can lead to higher savings rates, reduced debt burdens, and more sustainable economic participation, ultimately strengthening financial stability and economic resilience.